EFEITO ESQUISTOSSOMICIDA E IMUNOMODULADOR DE Dysphania ambrosioides (L.) MOSYAKIN & CLEMANTS NA INFECCÇÃO EXPERIMENTAL POR Schistosoma mansoni SAMBON, 1907. - RODRIGUES, João Gustavo Mendes (2019)
Schistosomiasis caused by the parasite Schistosoma mansoni, is a disease that arises from the granulomatous inflammatory response around the viable eggs of the parasite that are retained in the tissues of the host. Current chemotherapeutic agents are effective only against adult worms and do not reverse the inflammatory lesions caused by the parasitic process in the portal-hepatic system. In this way it is necessary to search for new treatments. Thus, this study evaluated the schistosomicidal and immunomodulatory effect of the hydroalcoholic extract of the leaves of Dysphania ambrosioides (EDA) against experimental infection by S. mansoni in Swiss mice. Initially, in vitro tests were performed with cercariae and adult worms exposed to different concentrations of the extract. Next, the in vivo evaluation was carried out, where mice were infected with 50 cercariae of S. mansoni at day 0 and euthanized 60 days after infection. For this assay, we used the following groups: positive control (infected animals with standard treatment), negative control (infected animals without treatment), clean control (uninfected or treated animals); (EDA1), pulmonary phase (EDA14), immature worms (EDA28), and mature worms (EDA45) were studied in the different stages of development of S. mansoni. In vitro, the EDA presented cercaricidal and schistosomicidal activity; In vivo, EDA presented, in the parasitological parameters, a reduction in the number of S. mansoni eggs in hepatic tissue and faeces; in immunological parameters, increased the number of lymphocytes, and induced reduction of eosinophils in the blood, reduced total IgE serum concentrations, increased cellularity of bone marrow and spleen, with significant increase in T helper, cytotoxic T, B lymphocytes and macrophages, increased numbers of neutrophils and reduced the number of mast cells in the peritoneal cavity, and did not reduce the production of hydrogen peroxide in the peritoneal cells; and in the histopathological parameters, reduced area and the amount of granulomas on the hepatic tissue. These results demonstrate EDA with antiparasitic and immunomodulatory action on the different stages of schistosomiasis, giving us the perspective to proceed with investigations of the effects and mechanisms of action of